Hubungan Keseimbangan dan Kekuatan Otot Tungkai terhadap Akurasi Passing pada SSB Bintang Laksono Usia 13-15 Tahun - Rizqi, Aditya; Tresnowati, Idah; Widya Putri, Mega; Panggaraita Lestari, Nuari (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The purpose of this study was to determine the relationship between muscle strength and balance with passing accuracy at the Bintang Laksono Football School (SSB) in Pekalongan Regency. Poor muscle strength and passing errors were the main problems in this study. A total of 22 players were sampled in this study, which combined purposive sampling techniques with a descriptive correlational design. Tests for kicking muscle strength, passing accuracy, and balance were some of the tools used. The results of the correlation test showed an R value of 0.963 with an R Square of 0.928 and a p value of <0.001, indicating a significant partial and simultaneous relationship between muscle strength, balance, and passing. Simultaneously, the passing accuracy of soccer players at Bintang Laksono SSB was influenced by balance and neck muscle strength.